2022
DOI: 10.3892/mmr.2022.12800
|View full text |Cite
|
Sign up to set email alerts
|

Interference of PTK6/GAB1 signaling inhibits cell proliferation, invasion, and migration of cervical cancer cells

Abstract: Protein tyrosine kinase 6 (PTK6) has shown important cancer-promoting effects in a variety of cancer types. Nonetheless, its vital role in cervical cancer has not been completely elucidated. The present study sought to address whether PTK6 is involved in the malignant progression of cervical cancer via its interaction with GRB2-associated binding 1 (GAB1). Western blotting was used to examine PTK6 and GAB1 expression levels. Cell Counting Kit-8, Transwell, wound healing, and terminal deoxynucleotidyl-transfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Overexpression of GAB1 was able to offset the inhibitory effects of PTK6 knockdown on cervical cancer cells. Cervical cancer cells were protected against the progression of malignant cervical cancer when PTK6 expression was knocked down [ 31 ]. Cagle and his group showed that the overexpression of miR-214 in prostate cancer cells led to the induction of apoptosis, which in turn inhibited cell proliferation and the ability to form colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GAB1 was able to offset the inhibitory effects of PTK6 knockdown on cervical cancer cells. Cervical cancer cells were protected against the progression of malignant cervical cancer when PTK6 expression was knocked down [ 31 ]. Cagle and his group showed that the overexpression of miR-214 in prostate cancer cells led to the induction of apoptosis, which in turn inhibited cell proliferation and the ability to form colonies.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma cell lines, GAB1 knockdown inhibited cell proliferation by reducing of ERK1/2 activation [ 95 ]. The absence of protein tyrosine kinase 6 (PTK6) expression reduces the proliferative capacity of cervical cancer cells and apoptosis induction in a GAB1-dependent manner [ 96 ]. HCK-mediated phosphorylation of GAB1 induces proliferation and survival in IL-6-induced multiple myeloma cells.…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%
“…Furthermore, GAB1 has been described to be upregulated to promote migration in anaplastic thyroid carcinoma cells through modulation of the AKT–Multidrug Resistance Protein 1 (MDR1) axis [ 117 ]. GAB1 overexpression increases migratory and invasive activity in cervical cancer cell lines [ 96 ]. Also, GAB1 has been reported to be closely involved in glioblastoma cell invasion through HGF-induced activation of dedicator of cytokinesis 7 (DOCK7) and RAC1 [ 118 ].…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers